Case Report: Disappearance of Late Gadolinium Enhancement and Full Functional Recovery in a Young Patient With SARS-CoV-2 Vaccine-Related Myocarditis - Korosoglou, Grigorios; Nunninger, Peter; Giusca, Sorin (Frontiers in Cardiovascular Medicine, 2022)
n/a (submission as an image vignette)